The Relationship Between Customer Satisfaction and Customer Loyalty in Online Environment - Devi Rosana Leonata (iBuss Management, 2015)
Many researches have already discussed about the relationship between customer satisfaction and customer loyalty. However, there is only few discussing about the relationship in online environment. Thus, this research is conducted to see whether there is significant relationship between customer satisfaction and customer loyalty in online environment as well as to know which best viewpoint that may describe the relationship. This research focuses on people who have done online transactions. The sampling method is simple random sampling and finally got 97 valid and reliable responses. Next, the valid data will be processed through several methods comprising Simple Linear Regression, Multiple Linear Regression, and Regression with Mediating Variable using SPSS Program. After going through several tests, the results of this research show that customer satisfaction has positive significance relationship to customer loyalty in online environment. Also, it is proven that the model with mediating variable, trust, may best define the relationship between customer satisfaction and customer loyalty in online environment.Keywords: Satisfaction, Loyalty, E-Commerce, Online Environment